Method for modifying coal gangue aggregate through coal ash-cement wrapping in cooperation with CO2 carbonization and modified coal gangue aggregate
Through the method of fly ash-cement wrapping and CO2 carbonization modified coal gangue aggregate, the problem of poor strengthening effect of existing modified coal gangue aggregate technology is solved, and the physical performance of coal gangue aggregate and CO2 storage is improved, which has good environmental protection and economic benefits.
Patent Information
- Application Number
- CN202411668262.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-04
AI Technical Summary
The existing modified coal gangue aggregate technology has problems such as poor reinforcement effect, high energy consumption, long processing time and complex process, which limits its application in concrete.
The method of coal gangue aggregates modified by fly ash-cement wrapping and CO2 carbonization is adopted to improve the physical properties of coal gangue aggregates by drying the saturated surface, mixing them with fly ash-cement slurry, and naturally drying them.
It effectively improves the apparent density, crush value and structural density of coal gangue aggregate, improves its mechanical properties and durability in concrete, and at the same time realizes the storage of CO2, which is green and environmentally friendly.
Smart Images

Figure CN119750941A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a method for modifying coal gangue aggregate by fly ash-cement encapsulation and coordinated CO2 carbonization, and the modified coal gangue aggregate. Background Art
[0002] At present, coal gangue is mainly used in power generation, production of organic fertilizers, and construction materials. Among them, applying coal gangue to the building materials industry and preparing it into aggregate for resource utilization can not only alleviate the pressure of the building materials industry on the demand for natural aggregates, but also alleviate the environmental pressure of coal gangue storage, which meets the current social development needs of green, low-carbon and sustainable development.
[0003] Due to the presence of a large number of microcracks, pores and a high carbon content in coal gangue, its water absorption rate and crushing value are high, and its apparent density is lower than that of natural aggregate. These defects lead to poor durability and mechanical properties of concrete when coal gangue is used as concrete aggregate, limiting its application in concrete. In order to improve the performance of coal gangue aggregate, many scholars have conducted research on the modification of coal gangue aggregate. The modification methods of coal gangue aggregate mainly include surface coating, thermal activation and microbial carbonization technology. The surface coating method mainly uses active mineral materials, nanomaterials and organic solvents to coat the coal gangue, and the coal gangue aggregate is modified by the reaction of active minerals with cement. The thermal activation method uses high temperature to activate kaolinite in coal gangue aggregate to modify it. Microbial carbonization technology uses microorganisms to induce carbonate precipitation to modify coal gangue aggregate. Although these studies have a certain effect on the enhancement and modification of coal gangue, the surface coating method has a poor strengthening effect in the later stage; the thermal activation method has high energy consumption, and the aggregate is easily cracked due to the influence of temperature stress; the microbial carbonization method takes a long time to treat the aggregate, and the early microbial cultivation process is complex and has many influencing factors. Many factors limit the promotion of these modification technologies in the utilization of coal gangue.
[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0005] The object of the present invention is to provide a method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization and modified coal gangue aggregate, so as to help improve the modification effect of coal gangue aggregate.
[0006] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization, comprising the following steps: (1) crushing coal gangue to obtain coal gangue aggregate; (2) subjecting the coal gangue aggregate to saturated surface drying treatment so that the coal gangue aggregate reaches a water absorption saturated state; (3) mixing the coal gangue aggregate obtained by the treatment in step (2) with fly ash-cement slurry evenly, then placing it on a sieve and drying it naturally to obtain coal gangue aggregate encapsulated by fly ash-cement slurry; (4) placing the coal gangue aggregate encapsulated by fly ash-cement slurry in a CO2 carbonization curing chamber for carbonization curing.
[0007] Preferably, in step (4), the temperature of the carbonization curing is 20±2° C., the relative humidity is 70%±5%, the CO2 concentration is 18%-22%, and the pressure is 0.09-0.11 MPa.
[0008] Preferably, in step (1), the particle size of the gangue aggregate is 4.75-9.5 mm; and in step (3), the aperture of the sieve is ≤4.75 mm.
[0009] Preferably, in step (3), the mass ratio of the coal gangue aggregate to the fly ash-cement slurry is 0.48-0.52.
[0010] Preferably, the fly ash-cement slurry is prepared by mixing cement, fly ash, a water reducing agent and water.
[0011] Preferably, in the fly ash-cement slurry: the cement is PO 42.5 ordinary Portland cement, the fly ash is primary fly ash, and the water reducer is a polycarboxylate water reducer.
[0012] Preferably, in the fly ash-cement slurry, the mass ratio of water to the total mass of fly ash and cement is 0.3-0.5; the amount of the water reducer is 0.245%-0.255% of the total mass of the fly ash-cement slurry; and the amount of fly ash is 9.5%-10.5% of the total mass of fly ash and cement.
[0013] The present invention also provides a modified coal gangue aggregate, which adopts the following technical scheme: a modified coal gangue aggregate is prepared by the method as described above.
[0014] Beneficial effects:
[0015] The present invention uses fly ash and cement to prepare fly ash-cement reinforced slurry, and uses CO2 carbonization technology to maintain the coal gangue aggregate wrapped by fly ash-cement slurry. It effectively utilizes fly ash and coal gangue solid waste, reduces environmental pollution, and saves resources. In addition, while strengthening the coal gangue aggregate, CO2 can be sealed. The specific analysis is as follows:
[0016] (1) SiO2, Al2O3 and other silicate glasses in fly ash react chemically with cement to produce Ca(OH)2, generating gels such as calcium silicate hydrate (CSH), which can improve the interface transition zone (ITZ) between the slurry and aggregate. Replacing part of the cement with fly ash to prepare the slurry for use as a surface coating material can not only save cement consumption and reduce carbon emissions, but the "ball effect" of fly ash can also improve the fluidity of the coated slurry.
[0017] (2) CO2 carbonization technology uses CO2 to react chemically with minerals to permanently embed CO2 into the mineral structure, thereby reducing the CO2 concentration in the atmosphere; CO2 can react with fly ash-cement paste to generate Ca(OH)2, CSH, AFt, and react with unhydrated C2S and C3S to generate CaCO3 and silica gel, thereby improving the pore structure and increasing the density of the coal gangue aggregate structure.
[0018] (3) Using coal gangue to prepare aggregate can solve the problem of aggregate shortage in the construction industry and contribute to the storage of CO2, thereby helping the coal gangue processing industry to improve its carbon emission reduction capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0020] Figure 1 The effects of different water-cement ratios and curing methods on the apparent density of gangue aggregate;
[0021] Figure 2 The effects of different water-cement ratios and curing methods on the water absorption of gangue aggregate;
[0022] Figure 3 The effects of different water-cement ratios and curing methods on the crushing value of coal gangue aggregates;
[0023] in, Figure 1-3 The "CGA" in the figure represents unmodified coal gangue aggregate (i.e., Comparative Example 1), "S-CGA" represents coated coal gangue aggregate under standard curing conditions (i.e., the coal gangue aggregate of Comparative Examples 2-6 with corresponding water-cement ratios), and "C-CGA" represents coated coal gangue aggregate under CO2 carbonization curing conditions (i.e., the modified coal gangue aggregate of Examples 1-5 with corresponding water-cement ratios). DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0025] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0026] In view of the problems existing in the current coal gangue aggregate, the present invention provides a method for modifying the coal gangue aggregate by fly ash-cement encapsulation and coordinated CO2 carbonization.
[0027] The method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization in an embodiment of the present invention comprises the following steps: (1) crushing coal gangue to obtain coal gangue aggregate; (2) performing saturated surface drying treatment on the coal gangue aggregate to make the coal gangue aggregate reach a water absorption saturated state; (3) mixing the coal gangue aggregate obtained by the treatment in step (2) with fly ash-cement slurry evenly, then placing it on a sieve and drying it naturally to obtain coal gangue aggregate encapsulated by fly ash-cement slurry; (4) placing the coal gangue aggregate encapsulated by fly ash-cement slurry in a CO2 carbonization curing chamber for carbonization curing.
[0028] The present invention adopts a method of fly ash-cement encapsulation and coordinated CO2 carbonization to modify coal gangue aggregate, which has the characteristics of being green and fixing carbon. The incorporation of fly ash into fly ash-cement slurry is different from the previous single slurry (cement slurry) encapsulation mechanism. While reducing costs, it fully utilizes the "ball effect" of fly ash to ensure the working performance of the slurry; the surfactant in fly ash can provide nucleation sites for cement hydration products, and utilizes the "volcanic ash effect" of fly ash to react with the hydration product Ca(OH)2 of cement to generate CSH gel, especially Ca(OH)2 enriched in the ITZ between coal gangue aggregate and reinforced slurry, thereby enhancing the encapsulation effect of fly ash-cement slurry. Under CO2 carbonization curing conditions, CO2 diffuses into the pore solution of coal gangue aggregate to form HCO3 - and CO3 2- , and carbonization reaction occurs with cement hydration products Ca(OH)2, CSH, etc. and unhydrated C2S, C3S, etc., to generate CaCO3 and silica gel, etc.; the volume of CaCO3 is 10%-12% larger than that of Ca(OH)2. Thus, the pore structure of coal gangue aggregate is refined, and the surface structure of coal gangue aggregate becomes denser. The fly ash-cement encapsulation and CO2 carbonization modification method can make coal gangue aggregate have better physical properties and denser microstructure, thereby producing more environmentally friendly, low-carbon, high-quality coal gangue aggregate.
[0029] In a preferred embodiment of the method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization of the present invention, in step (4), the carbonization curing temperature is 20±2°C (for example, 18°C, 19°C, 20°C, 21°C or 22°C), the relative humidity is 70%±5% (for example, 65%, 68%, 70%, 72%, 74% or 75%), the CO2 concentration is 18%-22%, and the pressure is 0.09-0.11MPa.
[0030] In a preferred embodiment of the method for modifying gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization of the present invention, in step (1), the particle size of the gangue aggregate is 4.75-9.5 mm; in step (3), the aperture of the sieve is ≤4.75 mm.
[0031] In a preferred embodiment of the method for modifying gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization of the present invention, in step (2), the gangue aggregate is subjected to a saturated surface drying treatment, which helps prevent the gangue aggregate from absorbing water in the reinforcing slurry (i.e., fly ash-cement slurry). The gangue aggregate is subjected to a saturated surface drying treatment before being encapsulated with the reinforcing slurry, so that the gangue aggregate reaches a saturated state of water absorption and surface impurities are cleaned off at the same time. If the gangue is packaged without saturated surface drying treatment, there will be the following effects: I. The gangue aggregate has many pores and absorbs water seriously, which will absorb water in the reinforced slurry (fly ash-cement slurry), seriously affecting the water-cement ratio of the reinforced slurry, resulting in incomplete hydration of the reinforced slurry, early powdering (water is absorbed by the aggregate, and the surface powder falls off after drying), and the actual water-cement ratio of each group of reinforced slurries is difficult to control; II. The surface of the gangue contains carbon, ash and other impurities. If the surface is not cleaned (the cleaning of the gangue can be achieved in the process of saturated surface drying of the gangue), it will affect the slurry coating effect and deteriorate the interface transition zone between the slurry and the aggregate; III. If the saturated surface drying treatment is not carried out, then during the packaging stage, the aggregate absorbs water in the reinforced slurry, causing the overall thickening, which is not conducive to packaging.
[0032] In a preferred embodiment of the method for modifying gangue aggregate by fly ash-cement coating and synergistic CO2 carbonization of the present invention, in step (3), the mass ratio of gangue aggregate to fly ash-cement slurry is 0.48-0.52. If the mass ratio of gangue aggregate to fly ash-cement slurry is too large (i.e., the amount of fly ash-cement slurry is too small), it is difficult to ensure uniform coating of fly ash-cement slurry on the surface of gangue aggregate during the mixing process of gangue aggregate and fly ash-cement slurry.
[0033] Preferably, in step (3), the mixing of the gangue aggregate and the fly ash-cement slurry is carried out in a mixer; the wrapped gangue aggregate is placed on a 4.75 mm sieve and dried naturally to prevent the gangue from clumping.
[0034] In a preferred embodiment of the method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization of the present invention, fly ash-cement paste is prepared by mixing cement, fly ash, water reducer and water. The water reducer can make the fly ash-cement paste more fluid and have a better encapsulation effect; if the water reducer is omitted, a larger water-cement ratio is required to achieve a comparable encapsulation effect, but if the water-cement ratio is increased, bubbles will be generated during the encapsulation process, and the evaporation of water after hardening will also leave many capillaries, thereby affecting the encapsulation effect.
[0035] In a preferred embodiment of the method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization of the present invention, in the fly ash-cement slurry, the cement is PO 42.5 ordinary Portland cement (preferably, with a specific surface area of 0.39 to 0.52 m 2 / g, calcium oxide content of 48.94% to 50.62%, silicon dioxide content of 23.43% to 25.48%); the fly ash is first-class fly ash (preferably, the specific surface area is 0.43 to 0.61 m 2 / g, calcium oxide content is 3.15% to 4.21%, silicon dioxide content is 50.23% to 52.87%); the water reducer is a polycarboxylic acid water reducer.
[0036] In a preferred embodiment of the method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization of the present invention, in the fly ash-cement slurry, the mass ratio of water to the total amount of fly ash and cement is 0.3-0.5 (for example, 0.3, 0.35, 0.4, 0.45 or 0.5); the amount of water reducer is 0.245%-0.255% (for example, 0.245%, 0.248%, 0.25%, 0.252% or 0.255%) of the total mass of the fly ash-cement slurry; the amount of fly ash is 9.5%-10.5% of the total mass of fly ash and cement.
[0037] The present invention also provides a modified coal gangue aggregate. The modified coal gangue aggregate in the embodiment of the present invention is prepared by the method as described above.
[0038] The method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization and the modified coal gangue aggregate of the present invention are described in detail below through specific embodiments.
[0039] In the following embodiments:
[0040] The gangue is produced by excavation in Jiaoxi Mine in Jiaozuo. Its chemical composition includes: SiO2 57.59%, Al2O3 21.31%, Fe2O3 6.51%, CaO 6.42%, K2O 3.51%, MgO 0.992%, Na2O 1.03% and SO3 0.734%; its water absorption rate is 3.03%, crushing value is 25.2%, and apparent density is 2495kg / m 3 ;
[0041] The water reducer is produced by Jiangsu Subote Company High-efficiency polycarboxylate water reducer, water reduction rate is 20%;
[0042] The cement is PO 42.5 ordinary Portland cement with a specific surface area of 0.39 to 0.52 m 2 / g, calcium oxide content is 48.94% to 50.62%, silicon dioxide content is 23.43% to 25.48%;
[0043] The fly ash is first-grade fly ash with a specific surface area of 0.43 to 0.61 m 2 / g, the calcium oxide content is 3.15% to 4.21%, and the silicon dioxide content is 50.23% to 52.87%.
[0044] Example 1
[0045] The method of fly ash-cement encapsulation and CO2 carbonization modification of coal gangue aggregate in this embodiment comprises the following steps:
[0046] (1) crushing and screening large pieces of coal gangue to select coal gangue aggregate with a particle size of 4.75 to 9.5 mm;
[0047] (2) In order to prevent the gangue aggregate from absorbing water from the strengthening slurry, the gangue aggregate is saturated and dried before being wrapped with the strengthening slurry, so that the gangue aggregate reaches the water absorption saturation state and the surface impurities are cleaned;
[0048] (3) preparing a fly ash-cement slurry with a water-cement ratio of 0.3 and a fly ash content of 10% (the mass ratio of coal gangue, cement, fly ash and water is 3:1:0.11:0.33, and the amount of water reducer is 0.25% of the total mass of the fly ash-cement slurry), mixing the pretreated coal gangue aggregate and the fly ash-cement slurry, and then placing the coated coal gangue aggregate on a 4.75 mm sieve, and drying it naturally to prevent the coal gangue from agglomerating, and finally obtaining the coal gangue aggregate coated with the fly ash-cement slurry;
[0049] (4) Finally, the wrapped gangue aggregate is placed in a CO2 carbonization curing box at a temperature of 20±2°C, a relative humidity of 70%±5%, a CO2 concentration of 20%, and a pressure of 0.1MPa for curing for 14 days to obtain the wrapped gangue aggregate under CO2 carbonization curing conditions (i.e., the modified gangue aggregate of this embodiment).
[0050] Example 2
[0051] The method of fly ash-cement encapsulation and synergistic CO2 carbonization modification of coal gangue aggregate in this embodiment is different from that in Example 1 only in that the water-cement ratio of the fly ash-cement slurry in step (3) is 0.35 (that is, the mass ratio of coal gangue aggregate, cement, fly ash and water is 3:1:0.11:0.39, and the amount of water reducer is 0.25% of the total mass of the fly ash-cement slurry); the rest is consistent with Example 1.
[0052] Example 3
[0053] The method of fly ash-cement encapsulation and synergistic CO2 carbonization modification of coal gangue aggregate in this embodiment is different from that in Example 1 only in that the water-cement ratio of the fly ash-cement slurry in step (3) is 0.4 (that is, the mass ratio of coal gangue aggregate, cement, fly ash and water is 3:1:0.11:0.44, and the amount of water reducer is 0.25% of the total mass of the fly ash-cement slurry); the rest is consistent with Example 1.
[0054] Example 4
[0055] The method of fly ash-cement encapsulation and synergistic CO2 carbonization modification of coal gangue aggregate in this embodiment is different from that in Example 1 only in that the water-cement ratio of the fly ash-cement slurry in step (3) is 0.45 (that is, the mass ratio of coal gangue aggregate, cement, fly ash and water is 3:1:0.11:0.5, and the amount of water reducer is 0.25% of the total mass of the fly ash-cement slurry); the rest is consistent with Example 1.
[0056] Example 5
[0057] The method of fly ash-cement encapsulation and synergistic CO2 carbonization modification of coal gangue aggregate in this embodiment is different from that in Example 1 only in that the water-cement ratio of the fly ash-cement slurry in step (3) is 0.5 (that is, the mass ratio of coal gangue aggregate, cement, fly ash and water is 3:1:0.11:0.56, and the amount of water reducer is 0.25% of the total mass of the fly ash-cement slurry); the rest is consistent with Example 1.
[0058] Comparative Example 1
[0059] The difference between the gangue aggregate in this comparative example and that in Example 1 is that the large pieces of gangue are crushed and sieved to obtain gangue aggregate with a particle size of 4.75-9.5 mm (that is, the gangue aggregate is not modified after being crushed to obtain the gangue aggregate).
[0060] Comparative Example 2
[0061] The difference between this comparative example and Example 1 is that the curing conditions are different (the curing conditions of this comparative example are: temperature 20±2° C., relative humidity above 95%); the rest are consistent with Example 1.
[0062] Comparative Example 3
[0063] The difference between this comparative example and Example 2 is that the curing conditions are different (the curing conditions of this comparative example are: temperature 20±2° C., relative humidity above 95%); the rest are consistent with Example 1.
[0064] Comparative Example 4
[0065] The difference between this comparative example and Example 3 is that the curing conditions are different (the curing conditions of this comparative example are: temperature 20±2° C., relative humidity above 95%); the rest are consistent with Example 1.
[0066] Comparative Example 5
[0067] The difference between this comparative example and Example 4 is that the curing conditions are different (the curing conditions of this comparative example are: temperature 20±2° C., relative humidity above 95%); the rest are consistent with Example 1.
[0068] Comparative Example 6
[0069] The difference between this comparative example and Example 5 is that the curing conditions are different (the curing conditions of this comparative example are: temperature 20±2° C., relative humidity above 95%); the rest are consistent with Example 1.
[0070] Experimental example
[0071] The basic physical properties (water absorption, crushing value, and apparent density) of the modified gangue aggregates of Examples 1-5 and Comparative Examples 1-6 were tested (according to the corresponding methods described in the national standard GB / T.14685-2022 "Pebbles and Crushed Stones for Construction"), and the specific data measured are shown in Table 1 and Figure 1-3 As shown:
[0072] Table 1 Basic physical properties of coal gangue aggregate in the embodiments and comparative examples
[0073]
[0074]
[0075] From Table 1 and Figure 1 It can be seen that after the gangue aggregate was coated with fly ash-cement slurry with different water-binder ratios, the apparent density increased (compared with Comparative Example 1); after the fly ash-cement slurry coating and CO2 mineralization synergistic treatment, the apparent density of the gangue aggregate increased more significantly; when the water-binder ratio increased from 0.3 to 0.5, the apparent density of the gangue aggregate showed a trend of first increasing and then decreasing; when the water-binder ratio was 0.35, the apparent density of the gangue aggregate coated with fly ash-cement slurry and synergistically treated with CO2 mineralization had the largest increase, which was increased by 3.85%.
[0076] From Table 1 and Figure 2 It can be seen that the water absorption rate of the gangue aggregate treated with fly ash-cement slurry with different water-binder ratios increased to a certain extent (compared with comparative example 1); after fly ash-cement slurry coating and CO2 mineralization synergistic treatment, the increase in the water absorption rate of the gangue aggregate was significantly reduced; when the water-binder ratio increased from 0.3 to 0.5, the water absorption rate of the gangue aggregate showed a trend of first decreasing and then increasing; when the water-binder ratio was 0.35, the water absorption rate of the gangue aggregate treated with fly ash-cement slurry coating and CO2 mineralization synergistic treatment had the lowest increase, which was only 9.9%.
[0077] From Table 1 and Figure 3 It can be seen that the crushing value of the gangue aggregate treated with fly ash-cement slurry with different water-binder ratios is greatly reduced (compared with Comparative Example 1); after fly ash-cement slurry coating and CO2 mineralization synergistic treatment, the crushing value of the gangue aggregate is reduced more significantly; as the water-binder ratio increases from 0.3 to 0.5, the crushing value of the gangue aggregate shows a trend of first decreasing and then increasing; when the water-binder ratio is 0.35, the crushing value of the gangue aggregate treated with fly ash-cement slurry coating and CO2 mineralization is reduced the most, by 29.37%; the crushing value of the modified gangue aggregate of Example 2 is 17.8%<20%, which meets the strength index requirements of the national standard GB / T.14685-2022 "Pebble and Crushed Stone for Construction".
[0078] In summary, the ecological aggregate prepared by the fly ash-cement encapsulation and CO2 carbonization modified coal gangue aggregate in the present invention has good physical properties and carbon fixation effect; the fly ash-cement slurry encapsulation and CO2 carbonization modified coal gangue aggregate with a water-cement ratio of 0.35 has an apparent density increased by 3.85% compared with the unmodified coal gangue aggregate, and the crushing value is reduced by 29.37%, and its crushing value is 17.8% <20%, which meets the strength index requirements of the national standard GB / T.14685-2022 "Pebble and Crushed Stone for Construction", and is suitable for use in mining concrete, road construction, building decoration, environmental protection engineering and other fields.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization, characterized in that: The steps include: (1) crushing the coal gangue to obtain coal gangue aggregate; (2) performing a saturated surface drying treatment on the gangue aggregate so that the gangue aggregate reaches a water absorption saturation state; (3) mixing the gangue aggregate obtained by the treatment in step (2) with fly ash-cement slurry evenly, and then placing it on a sieve and drying it naturally to obtain the gangue aggregate coated with fly ash-cement slurry; (4) Placing the coal gangue aggregate wrapped in the fly ash-cement slurry in a CO2 carbonization curing chamber for carbonization curing.
2. The method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization as claimed in claim 1, characterized in that: In step (4), the temperature of the carbonization curing is 20±2° C., the relative humidity is 70%±5%, the CO2 concentration is 18%-22%, and the pressure is 0.09-0.11 MPa.
3. The method for modifying coal gangue aggregate by fly ash-cement encapsulation and CO2 carbonization as claimed in claim 1, characterized in that: In step (1), the particle size of the coal gangue aggregate is 4.75-9.5 mm; In step (3), the aperture of the sieve is ≤4.75 mm.
4. The method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization as claimed in claim 1, characterized in that: In step (3), the mass ratio of the coal gangue aggregate to the fly ash-cement slurry is 0.48-0.
52.
5. The method for modifying coal gangue aggregate by fly ash-cement encapsulation and synergistic CO2 carbonization as claimed in claim 1, characterized in that: The fly ash-cement paste is prepared by mixing cement, fly ash, a water reducing agent and water.
6. The method for modifying coal gangue aggregate by fly ash-cement encapsulation and CO2 carbonization as claimed in claim 5, characterized in that: In the fly ash-cement slurry: the cement is PO 42.5 ordinary Portland cement, the fly ash is first-grade fly ash, and the water reducer is a polycarboxylate water reducer.
7. The method for modifying coal gangue aggregate by fly ash-cement encapsulation and CO2 carbonization as claimed in claim 2, characterized in that: In the fly ash-cement slurry, the mass ratio of water to the total amount of fly ash and cement is 0.3-0.5; The amount of the water reducing agent is 0.245%-0.255% of the total mass of the fly ash-cement paste; The amount of fly ash used is 9.5%-10.5% of the total mass of fly ash and cement.
8. A modified coal gangue aggregate, characterized in that: The method is prepared by the method described in claims 1-7.
Citation Information
Patent Citations
Preparation method for coal gangue aggregate no-sand porous plant-growing concrete
CN107857528A
Coal gangue type concrete and preparation method thereof
CN115925367A
Carbonization-cured high-strength coal gangue-based low-carbon baking-free grass planting brick and preparation method thereof
CN116119990A
Coal gangue coarse aggregate strengthening technology
CN117819856A
Preparation method of all-solid-waste carbonization curing baking-free brick and carbonization curing equipment
CN118063188A